Assessment of the Adequacy of Gauge Repeatability and Reproducibility Study Using a Monte Carlo Simulation. (15th August 2017) - Ha, Chunghun; Kim, David S.; Park, SeJoon
Abstract : ANOVA gauge repeatability and reproducibility study is the most popular tool for measurement system analysis. Two experimental designs can be applied depending on the durability of the objects. If repeated measurements are possible or sufficient homogeneous nonrepeatable samples are available, crossed design is appropriate; otherwise, nested design should be used. In this paper, we investigated the adequacy of ANOVA gauge repeatability and reproducibility study from the perspective of practitioners. We proposed a Monte Carlo simulation that is close to the realistic procedure to evaluate the adequacy of both structures. During the evaluation, we considered the average performance metrics, percentage of correct decision, histogram shape, and symmetric mean absolute percentage error for the four popular performance metrics, namely, % Study Variation, % Contribution, % Tolerance, and the number of distinct categories. The experimental results show that the nested design fails to judge the precision of the gauge while the crossed design succeeds.